«Marshall Plan» for Donbass: prerequisites for investment development - Kolosov, A.; Kolosova, K.; Savchenko, O.; Kucherenko, S. (Економічний вісник Донбасу, 2018)
The preconditions for restoration and investment development of Donbass according to the international "Marshall Plan" in case of peaceful settlement of armed conflict are determined. Significant advantages of Donbass as an object of the Marshall Plan implementation are shown, in particular, depending on the stages of the peaceful settlement in the Donbass, as well as the directions of investment of the enterprises of the largest cities of Donbas. The proposed estimation of volumes of annual investments, receipt of additional products, possibilities of its immediate consumption is offered. Визначено передумови відновлення й інвестиційного розвитку Донбасу згідно з міжнародним «Планом Маршалла» у разі мирного врегулювання збройного конфлікту. Показано суттєві переваги Донбасу як об’єкту запровадження «плану Маршалла», зокрема, у залежності від етапів мирного врегулювання в Донбасі, а також напрямки інвестування підприємств найбільших міст Донбасу. Запропоновано укрупнену оцінку обсягів щорічних інвестицій, отримання додаткової продукції, можливості її негайного споживання. Определены предпосылки восстановления и инвестиционного развития Донбасса в соответствии с международным «Планом Маршалла» в случае мирного урегулирования вооруженного конфликта. Показаны существенные преимущества Донбасса как объекта осуществления «плана Маршалла», в частности, в зависимости от этапов мирного урегулирования в Донбассе, а также направления инвестирования предприятий крупнейших городов Донбасса. Предложена укрупненная оценка объемов ежегодных инвестиций, получения дополнительной продукции, возможности ее немедленного потребления.